The Influence of Sustainability Orientation and Green Promotion on Marketing Performance and Brand Reputation of Green MSMEs in Bandung - Feliks Anggia Binsar Kristian Panjaitan; Rani Eka Arini; Dila Padila Nurhasanah (West Science Interdisciplinary Studies, 2026)
This study aims to analyze the effect of sustainability orientation and eco-friendly promotion on marketing performance and brand reputation of eco-friendly miscro, small and medium-sized enterprises (MSMEs) in Bandung. In the context of increasing environmental awareness and competitive market dynamics, MSMEs are required to adopt sustainable practices and communicate them effectively to enhance both performance and public perception. This research employs a quantitative approach using primary data collected from 180 MSMEs owners and managers through a structured questionnaire based on a Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 3. The results indicate that sustainability orientation has a positive and significant effect on marketing performance and brand reputation. Eco-friendly promotion also shows a significant and stronger influence on marketing performance and brand reputation. Furthermore, marketing performance has a positive effect on brand reputation and serves as a mediating variable in the relationship between sustainability orientation, eco-friendly promotion, and brand reputation. The model demonstrates strong explanatory and predictive power, indicating that sustainability-driven strategies are critical for enhancing business outcomes. This study contributes to the literature by providing empirical evidence on the integration of sustainability and marketing strategies in MSMEs, particularly in developing countries. Practically, the findings offer strategic insights for MSMEs owners to improve competitiveness and long-term brand value through sustainable practices.